The Role of Autonomous Shipping in Revolutionizing Global Maritime Transport - Zewdu Mekonnen Fikru; Kebede Yohannes (Indonesian Maritime Researchers and Lecturers, 2025)
The advent of autonomous shipping is poised to revolutionize global maritime transport by enhancing efficiency, safety, and sustainability. This study investigates the current state and future prospects of autonomous vessels in the shipping industry. The primary objective is to analyze the technological advancements, regulatory challenges, and economic implications associated with the integration of autonomous ships. A mixed-methods approach, combining qualitative and quantitative research, was employed, including a review of relevant literature and case studies of existing autonomous shipping projects. The findings reveal that while autonomous ships offer significant benefits such as reduced operational costs, lower emissions, and fewer human errors, there are challenges related to legal frameworks, cybersecurity, and public acceptance. The implications of this research highlight the need for international cooperation and the development of new regulations to support the widespread adoption of autonomous shipping technologies. This transformation could lead to a more efficient, environmentally friendly, and cost-effective global maritime transport system.